The Career Choice Reasons of Special Education Teacher Candidates - Sezgin Vuran; Kürşat Öğülmüş; Murat Hikmet Açıkgöz (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: Special education teaching has become a popular and frequently preferred profession in recent years. It is a matter of curiosity why this profession is preferred. The aim of the study is to examine the reasons for the preference of pre-service teachers the special education department. Method: In this study, phenomenology, one of the qualitative research models has been used. The participants of the study consisted of 182 first-year students of special education teacher training program studying in four different universities in the Black Sea and Central Anatolia regions. The data of the study were collected online through a data collection form created by the researchers. The data were analyzed with MAXQDA software. Findings: According to the findings, the students preferred the special education department for altruistic reasons, felt positive feelings towards the department, and set personal goals for their profession in the future. Most of the students did research before choosing the department and received information from people related to special education. It was concluded that the people who influenced the students to choose the department were mostly family members. Finally, most of the students stated that they found special education teaching suitable for their personalities. Discussion: When the results of the research are evaluated in general, it is seen that special education teacher training program is mostly preferred for altruistic reasons and that the preferences are mostly researched and made consciously. This situation is thought to be important and promising in terms of students' future professional success